THE MOVING OF EMOTION ON ELDERLY' S LIFE: A STUDY WITH A THIRD AGE GROUP - Fabíola Braz Penna; Fátima Helena do Espírito Santo (Universidade Federal de Goias, 2006)
ABSTRACT: Qualitative study which aims was to describe the emotions in elderly life and to debate the relation between emotions and elderly health. The study was developed in a third age group at Sao Gonçalo city - RJ by participant observation and semi-structured interviews with ten elderly people. After the information analysis it was possible to identify the category "The Pendulum of Emotions" and two complementary subjects: rising and descending movement of emotions on living. The elderly evidenced that their emotions represents a continuous movement which reflects straightly to the feeling of being or not healthy and living well the third age is having autonomy of daily activities and freedom to participate of leisure and physical activities. Thus, the human being needs to valorize all the stages of his life, because the process of becoming old starts from the moment we were born and the quality of life is a daily conquest in this way. KEY WORDS: Aging; Mental Health; Quality of Life.